PENTINGNYA PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DALAM MENCEGAH PENYAKIT DIARE SETELAH BANJIR DI PONDOK PESANTREN SEJAHTERA - Unaisah Annufaisah Nuh Siregar; Susilawati; Natya Amelya Yahya; Della Septiana Syabania (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Flooding increases the risk of waterborne infectious diseases, including diarrhea, especially in densely populated environments such as Islamic boarding schools. The implementation of Clean and Healthy Living Behaviors (PHBS) is an important strategy in preventing diarrhea after flooding. This study aims to analyze the implementation of PHBS in efforts to prevent diarrhea among students at the Sejahtera Islamic Boarding School after flooding. The method used in this study was a descriptive quantitative method with a cross-sectional approach conducted on 50 students using total sampling techniques. Data analysis used descriptive 2 statistics and the Chi-Square test. The results showed that the majority of students implemented PHBS well in terms of hand washing (96%), use of clean water (90%), and consumption of healthy food (78%). However, 42% of students still experienced diarrhea after the flood. Bivariate analysis showed no significant relationship between the three components of PHBS and the incidence of diarrhea (p>0.05). Although the implementation of PHBS by students was in the good category, the incidence of diarrhea still occurred in some respondents, indicating the need for a comprehensive approach involving improvements in environmental sanitation and consistent improvement in the quality of PHBS implementation.